Peripartum Cardiomyopathy (PPCM) : Case Report and Review of Literatures - Sudarman, Befrie Mahaztra (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Introduction: Peripartum cardiomyopathy (PPCM) is a disease characterized by an enlargement of the heart muscle wall. The disease occurs in the last month of pregnancy up to 5 months postpartum, with no previous history of heart disease. The etiology of the disease is unclear. Early recognition of this case can lead to decrease in morbidiy and mortality. Case: A 20-year-old woman came to the Emergency Unit with a shortness of breath. There is a history of give birth about 4 months ago. Physical examination shows a regular heart rhythm accompanied by rhonchi sound in the basal aspect of lung. In the M-mode analysis of ECG showed left ventricular systolic ejection function is decrease (56.5%) while the right ventricle is normal. In the Hospital, patient get treated with diuretics, aldosterone antagonist, angiotensin II receptor blocker and fluid management. Patient gave good responsed to the therapy regiment. Discussion: The early clinical manifestations of PPCM are difficult to recognize. In the majority of patients, 78% of symptoms are found at 4 months after delivery, only 9% of patients show symptoms in the last month of pregnancy. Clinical symptoms include atypical chest pain, abdominal discomfort, signs of pulmonary edema, orthopnea and paroxysmal nocturnal dyspnea. In the management of patients with PPCM is almost similar to management in other congestive heart disease.